Study of ChatGPT Utilization Behavior by Accounting Education Students: Extended UTAUT2 Model Perspective - Rediana Setiyani; Jarot Tri Bowo Santoso; Ahmad Nurkhin; Siti Fatimah (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2025)
The use of Generative Artificial Intelligence (GAI), such as Chat Generative Pre-Trained Transformer (ChatGPT), is experiencing a significant increase among students for educational purposes, including lectures, completing assignments, and compiling final projects. This study aims to analyze the use of ChatGPT by accounting education students and investigate their intentions and behavior using the extended Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) framework. The study employed Partial Least Squares Structural Equation Model (PLS-SEM) analysis design with respondents from Accounting Education students at the Faculty of Economics and Business, Universitas Negeri Semarang (UNNES), totaling 134 students. The data collection technique used was a questionnaire distributed online via the Google Forms platform. Model testing was conducted first, followed by hypothesis testing in the PLS-SEM framework. Data analysis was conducted using the SmartPLS version 4.0 application. The results of the study showed that students' intention to use ChatGPT was more determined by performance expectancy and habit. Intention, facilitating conditions, and habits are significant predictors of use behavior. Intention can mediate the influence of habit on the actual behavior of students utilizing ChatGPT. In addition, extended-UTAUT2 constructs such as personal innovativeness, learning value, and novelty are unable to influence the intention and behavior of ChatGPT utilization by accounting education students.